2022
DOI: 10.3389/fonc.2022.1107271
|View full text |Cite
|
Sign up to set email alerts
|

Corrigendum: Identification and management of aggressive meningiomas

Abstract: In the published article, there was an error in Figure 1. All locations in the figure that mention "TRAF4" are incorrect and should be changed to "TRAF7". The corrected Figure 1 and its caption (unchanged) appear below.The authors apologize for this error and state that this does not change the scientific conclusions of the article in any way. The original article has been updated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A previous study reported that a meningioma with telomerase reverse transcriptase promoter mutations harbors a higher risk of malignant transformation and a more aggressive clinical course compared to meningioma without (TERT) promoter mutations ( 17 ). Furthermore, another study demonstrated that a neurofibromatosis type 2 mutation activated the Hippo, Notch, PI3K/AKT, mTOR and RAS/MAPK signaling pathways, with an ensuing increase in cell proliferation ( 18 ). In addition, some studies have found that stereotactic radiosurgery ( 19 ), surgical stress ( 16 ) and viral infection ( 4 ) can induce the malignant transformation of intracranial meningioma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous study reported that a meningioma with telomerase reverse transcriptase promoter mutations harbors a higher risk of malignant transformation and a more aggressive clinical course compared to meningioma without (TERT) promoter mutations ( 17 ). Furthermore, another study demonstrated that a neurofibromatosis type 2 mutation activated the Hippo, Notch, PI3K/AKT, mTOR and RAS/MAPK signaling pathways, with an ensuing increase in cell proliferation ( 18 ). In addition, some studies have found that stereotactic radiosurgery ( 19 ), surgical stress ( 16 ) and viral infection ( 4 ) can induce the malignant transformation of intracranial meningioma.…”
Section: Discussionmentioning
confidence: 99%
“…Some researchers have found that gamma knife radiosurgery may be an effective therapy for the first recurrence of transitional meningioma ( 10 ). Observation is another option, generally reserved for small, asymptomatic tumors and for patients that are deemed poor candidates for other therapeutic options ( 18 ). The management of these patients requires observation and serial monitoring with MRI scans.…”
Section: Discussionmentioning
confidence: 99%